Coding of Reward Probability and Risk by Single Neurons in Animals - Burke, Christopher J.; Tobler, Philippe N. (Frontiers in Neuroscience, 2011)
Probability and risk are important factors for value-based decision making and optimal foraging. In order to survive in an unpredictable world, organisms must be able to assess the probability and risk attached to future events and use this information to generate adaptive behavior. Recent studies in non-human primates and rats have shown that both probability and risk are processed in a distributed fashion throughout the brain at the level of single neurons. Reward probability has mainly been shown to be coded by phasic increases and decreases in firing rates in neurons in the basal ganglia and midbrain. By contrast reward variance is represented in orbitofrontal and posterior cingulate cortex and through the sustained response of dopaminergic midbrain neurons.